The Effectiveness of the Empowerment Program on Knowledge, Attitude, and Consumption Behavior Associated with Cholangiocarcinoma - Pamulila, Sompong; Dockphut, Sawai; Paprom, Wassamon; Wamaloon, Chaliya (Journal of The Royal Thai Army Nurses, 2021)
The objective of this quasi-experimental study was to study the effectiveness of the empowerment program on knowledge, attitude, and consumption behavior associated with cholangiocarcinoma using Roy’s adaptation theory and Gibson’s empowerment concept. The samples consisted of 40 people at risk of cholangiocarcinoma. They were equally divided into the control group and the experimental group. The experimental group received nursing activities individually to empower for 45-60 minutes each time for 6-8 days in a row. The research instrument was the empowerment program, consiting of 5 activities. The data were collected by using the questinnaire on knowledge, attitude and consumption behavior associated with cholangiocarcinoma. The data were analyzed by independent t-test and paired t-test. The results were as follows. (1) The mean scores of knowledge, attitude, and consumption behavior associated with cholangiocarcinoma of the people at risk of cholangiocarcinoma who were empowered were higher than those of the people at risk of cholangiocarcinoma who were not empowered with statistical significance at the level of .01. (2) The mean scores of knowledge, attitude, and consumption behavior associated with cholangiocarcinoma of the people at risk of cholangiocarcinoma who were empowered were higher than those of before being empowered with statistical significance at the level of .01. It can be seen that empowerment is a nursing activity that promotes and increases knowledge and attitude and modifies people’s consumption behavior associated with cholangiocarcinoma.